Forest health mapping in Gunung Basor permanent forest reserve by using unmanned aerial vehicle - Maizatul Afiqah Mohd Zaki (2019)
Unmanned Aerial Vehicle (UAV) is widely use in monitoring the forest and agriculture. The importance of this study was to determine the condition of the forest (healthy or unhealthy) and to mapping the forest health using Unmanned Aerial Vehicle UAV (drone) in Gunung Basor Permanent Forest Reserve. Furthermore, advanced of technology in UAV would hasten the study and yield the result with full coverage of the forest. There was no previous study that has been done to ensure the forest health at Gunung Basor Permanent Forest Reserve. The DJI Phantom 4Pro was used to capture the image of the study area by using Pix4D, and the image will be process in Data Mapper by using VARI algorithm. Besides that, to verify the data obtain from VARI Ground truth was conducted within the area. Based on observation, the forest is alive but not very healthy it verifies by the ground truth that total of necromass is higher than total of individual tree in the area.